UNVEILING THE COLLABORATIVE LANDSCAPE: EXPLORING PHARMACY TECHNICIANS' PERCEPTIONS AND EXPERIENCES OF INTERPROFESSIONAL TEAMWORK IN ENHANCING MEDICATION SAFETY - Faisal Lazzam Alshammari, Faisal Awad Alshammari, Nawaf Mohammed Alshammari, Neda Muhna Alshammari, Taysir Ibrahim Alshammari, Abdullah Hadyan Almutairi, (Chelonian Research Foundation, 2022)
Medication errors continue to be a significant patient safety concern, and interprofessional collaboration has been identified as a key strategy for reducing these errors. Pharmacy technicians play a crucial role in the medication use process and are well-positioned to collaborate with other healthcare professionals to enhance medication safety. This qualitative study aimed to explore pharmacy technicians' perceptions and experiences of interprofessional teamwork in promoting medication safety in a tertiary hospital in Riyadh, Saudi Arabia. Semi-structured interviews were conducted with 15 pharmacy technicians, and the data were analyzed using thematic analysis. Four main themes emerged: 1) understanding interprofessional collaboration, 2) perceived benefits of interprofessional teamwork for medication safety, 3) challenges to effective interprofessional collaboration, and 4) strategies to foster interprofessional teamwork. The findings highlight the importance of effective communication, role clarity, mutual trust, and organizational support in promoting interprofessional collaboration among pharmacy technicians and other healthcare professionals. The study provides valuable insights for healthcare organizations, educators, and policymakers to develop interventions and policies that support interprofessional teamwork and improve medication safety in the Saudi context. Keywords: interprofessional collaboration, medication safety, pharmacy technicians, qualitative research, Saudi Arabia